METHODS OF NOISE LEVEL REDUCTION OF DRIVE IN LATHES - Janusz ROGULA (Scientific Journal of Silesian University of Technology. Series Transport)
The aim of this work is method presentation to noise level reduction of fixed headstock of the lathe. It is connected with the causes finding of non-uniform work of lathe headstock, description of recent design and its analysis. Problem of the excessive noise level concern to near 35% of the lathes have been produced. In spite of lack of noise reduction possibility there were no system solution of problem. Design optimisation weren’t done after application the electric motor with inverter. New solution of electric motor control let to reduce number of gear wheels in lathe drive system. For this drive solution there weren’t made the analysis of drive particular parts influence on the noise generation.